(3MbjHI JOQjHjI dJfejI GdEHOGY GdEOGQjs - (3SgjdI(B, (3YHGSs ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2004)
(3GdebheGJ GdefWbjI ddbjGOI GdGHJcGQjI,fXQjGJ hfeGPL GdbGOI,GdbjGOI hOGjfejcjI GdYed GdLeGYj,CSS GdbjGOI GdaYGdI daQb GdYed,MGdGJ Mhd LeGYGJ haQb GdYed,ebheGJ GdCOGA GdeJejR ddCaQGO hGdefXeGJ,MGdGJ Yf GdCOGA GdeJejR hGdGHOGYj,GdeSDhdjI hGdbhI hGdbOQI dbjGOJg,GdJejjR hGdLhOI,efXeGJ GdJYde hGdGHOGY,egGQGJ GdJNWjW GdGSJQGJjLj hGdEHOGY,GdLhOI hQVG GdRHGFfs
(3HHdjhZQGajG(B:(3U(B.193-194s
Keywords: (3EOGQI GdCaQGOs; (3GdGOGQIs; (3GdJfejI GdGOGQjIs